21st century tundra shrubification could enhance net carbon uptake of North America Arctic tundra under an RCP8.5 climate trajectory. (14th May 2018) - Mekonnen, Zelalem A; Riley, William J; Grant, Robert F
Abstract: Recent observed shifts in Arctic tundra shrub cover have uncertain impacts on 21st century net ecosystem carbon exchanges. Here we applied a well-tested ecosystem model, ecosys, to examine the effects of North America Arctic tundra plant dynamics on ecosystem carbon balances from 1980–2100 under the RCP8.5 scenario. Tundra productivity was modeled to increase from enhanced carbon fixation and N mineralization under recent and future climates. Between 1982 and 2100 and averaged across the region, predicted increases in relative dominance of woody versus non-woody plants increased ecosystem annual net primary productivity by 244 g C m −2 that offset concurrent increases in annual heterotrophic respiration (139 g C m −2 ), resulting in an increasing net carbon sink over the 21st century. However, smaller increases in seasonal carbon uptake during winter (1 g C m −2 ) and autumn (22 g C m −2 ) and greater increases in ecosystem respiration (winter (23 g C m −2 ) and autumn (47 g C m −2 )) by 2100 versus 1982 resulted in larger carbon losses during these seasons that completely offset the gains in spring (13 g C m −2 ) and 25% of the gains in summer (140 g C m −2 ). Modeled soil temperatures were predicted to increase more slowly than air temperatures ( 0.6 °C for every 1 °C increase in air temperature over the 21st century). This slower soil versus air warming, and thus greater increases in CO2 fixation versus soil respiration rates, also contributed to the tundra remaining a carbon sink through 2100. However, these higher gains versus losses of carbon may be a transient response and not sustainable under further soil warming beyond 2100. Our modeling analysis allows us to extend beyond results from short-term warming experiments, which cannot characterize effects associated with decadal-scale changes in plant communities.